DRIVERLESS FUTURE? - GREENHOUSE, STEVEN (American Prospect)
The article offers information related to the world of driverless cars and trucks. It is noted that Uber's co-founder and Chief Executive Officer (CEO) Travis Kalanick is very high on driverless technology, by stating that when there is no driver in the car, the cost of taking an Uber anywhere becomes cheaper than owning a vehicle. It also discusses steps taken by various automobile manufacturing firms like Ford Motor and General Motors to have driverless cars on the road.